EVALUASI EFISIENSI DAN KINERJA MESIN RIPPLE MILL KAPASITAS 8 TON/JAM DALAM PENGOLAHAN KELAPA SAWIT - Sipayung, Evraim; Zuliantoni; Puspawan, Angky (UNIB Press, 2025)
Oil palm is a plant that produces palm oil which is widely known as Crude Palm Oil (CPO). Palm oil is refined into crude palm oil (CPO) and palm kernel. Kernel quality parameters include dirt content, water content and percentage of broken kernels. The kernel breaking process uses a Ripple mill machine. The Ripple mill machine is a part that determines the quality of the kernel in production at the kernel station and causes problems when the machine does not work effectively. Common problems faced by companies are frequent sudden machine breakdowns and production results do not meet the specified production criteria. In analyzing machine performance, both production and machine efficiency, the method is carried out by taking samples at the chute sampling point every 2 hours while the machine is operating with different sample weights. The sample is stirred until homogeneous so that whole nuts, broken nuts and broken kernels do not pile up. Then the sample is divided into four or quarts, take two opposite parts and put them in a container. The sample is weighed with a sample weight of 1 kg, pour the sample for analysis by separating whole nuts, broken nuts, and broken kernels. Then weigh the whole nuts and broken nuts, record the weighing results, from the weighing results do calculations using the formula to determine the efficiency of the Ripple mill.